2007
DOI: 10.1364/ao.46.008052
|View full text |Cite
|
Sign up to set email alerts
|

Transfer matrix analysis of the unidirectional grating-assisted codirectional coupler

Abstract: The unidirectional grating-assisted codirectional coupler (U-GACC) has recently been proposed. This unique structure permits irreversible coupling between orthogonal waveguide eigenmodes by means of simultaneous modulation of both the real and imaginary parts of the refractive index in the coupling region. Analysis of the U-GACC has until now relied on coupled mode theory, which can be restrictive in its application as a design tool. We analyze the U-GACC by the transfer matrix method, which demonstrates in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Interestingly, the first studies of couplers with modulated loss and gain were carried out without a consideration of PT symmetry [186][187][188][189]. In these studies, it was shown that unidirectional energy transfer between co-propagating optical modes can be achieved in waveguides with longitudinally modulated gain and loss regions.…”
Section: Modulated Waveguide Couplersmentioning
confidence: 99%
“…Interestingly, the first studies of couplers with modulated loss and gain were carried out without a consideration of PT symmetry [186][187][188][189]. In these studies, it was shown that unidirectional energy transfer between co-propagating optical modes can be achieved in waveguides with longitudinally modulated gain and loss regions.…”
Section: Modulated Waveguide Couplersmentioning
confidence: 99%
“…This allows us to eliminate the terms proportional to K 13 and K 31 . With these simplifications, (7) can be re-written as (8) with self-coupling terms (9a) non-reciprocal cross-coupling terms (9b) and reciprocal cross-coupling terms (9c) Eqns. (9) provide a clear picture of the coupling characteristics of this structure when compared with (5).…”
Section: Blocking Of the Spurious Modementioning
confidence: 99%
“…The non-reciprocal (NR) waveguide grating has recently been proposed and analyzed in theory [1][2][3][4][5][6][7][8]. In a NR grating, the coupling strength between two modes is made unequal through the use of a complex-valued longitudinal index perturbation; one that has a real part, equivalent to a standard index grating, and an imaginary part, equivalent to a gain / loss grating.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations